RANCANG BANGUN SISTEM SENSOR OTOMATIS PADA ALAT PENERANGAN JALAN (APJ) DI JALAN BUKIT DHARMA RAYA JIMBARAN - I Wayan Darsana; I Wayan Sukerayasa; Cokorde Gede Indra Partha (Jurnal SPEKTRUM, 2025)
Street lighting plays a crucial role in supporting public safety and comfort, especially at night. However, many areas, such as Jalan Bukit Dharma Raya Jimbaran, still lack adequate lighting systems. This study designs and implements an intelligent street lighting system based on the Internet of Things (IoT), utilizing the ESP32 Devkit V1 as the central controller, along with an LDR sensor, ultrasonic sensor, and an AC Light Dimmer to automatically adjust light intensity according to time and traffic conditions. Test results show that the system operates efficiently and adaptively, achieving energy savings of up to 17.6% and cost savings of Rp 54.39 compared to a manual system, with efficiency levels varying depending on road user activity. The prototype has proven effective in enhancing energy efficiency and offers an adaptive lighting solution that can be further developed to support the concept of a sustainable smart city.